THE PREVALENCE AND RELATION OF OVINE PROGRESSIVE PNEUMONIA TO PASTEURELLA HAEMOLYTICA IN TWO FLOCKS OF SHEEP - Badri Abboud, Hayder (The Iraqi Journal of Veterinary Medicine, 1988)
The incidence of ovine progressive pneumonia (OPP), and its relation to Pasteurella haemolytica in two naturally infected flocks of sheep of different ages was studied. The Ager Gel Immunodiffusion test was used for testing for OPP. Nasal Swabs were taken for the isolation of P. haemolytica. Four ewes were necropsied, anu both gross and histopathological examinations were done. A few seronegative sheep sero-converted and the seropositive sheep remained positive. Seropositive sheep did not develop clinical illness or lesions of the disease at Lambing (stress factor) necropsy. to predisposes infection with OPP. Infection with OPP predisposes sheep for secondary bacterial infection with P. haemolytica.